Development of Open Transport of Aqueous Fluid from Pegmatite Revealed by Trace Elements in Garnet - Astin Nurdiana; Atsushi Okamoto; Masaoki Uno; Noriyoshi Tsuchiya (Geofluids)
We investigated the fluid flow and elemental transport from a granitic body to the middle crust by determining the trace element compositions of garnet in pegmatites related to a quartz diorite intrusion and metamorphic rocks on Kinkasan Island, northeast Japan. Garnet in the pegmatites and biotite schists is characterized by spessartine– (Sps–) almandine- (Alm-) rich compositions of Sps14–69Alm22–70Prp2–14Grs1–13 and Sps16–30Alm54–66Prp9–16Grs3–6, respectively. A garnetite pod in the metamorphic unit has grossular- (Grs-) rich compositions (Sps1–4Alm8–11Prp0.1–0.4Grs80–87Adr3–4). The peak temperature (T) and pressure (P) conditions of the biotite schist during contact metamorphism were 600–650°C and 0.27–0.41 GPa, respectively. The primary fluid inclusions in quartz crystals within the pegmatites hosted by the quartz diorite and hosted by the metamorphic rocks have a wide range of homogenization temperatures (200–380°C). These correspond to the trapping temperature of 500–700°C, assuming a salinity of 4 wt.% NaClequivalent at pressure of the crystallization of the quartz diorite. Chondrite-normalized rare earth element (REE) patterns of garnets in the pegmatites in the quartz diorite and metamorphic unit are generally characterized by enrichment of heavy REEs and negative Eu anomalies with the REE contents in the schists which are systematically lower than in the pegmatites. However, garnet in the biotite schists close to the pegmatites has similar REE contents to garnet in the adjacent pegmatites. These geochemical features suggest that garnet in the biotite schists grew in response to fluid infiltration from the pegmatites. Besides, the Grs-rich garnet in the garnetite pod and its host quartz schist have flat heavy REE patterns and no Eu anomalies, which probably reflect a metasomatic process related to plagioclase replacement that produced Ca-Al-rich fluids. Our results suggest that the infiltration of pegmatitic fluids enhances elemental transport and metamorphic reactions in the middle crust.